Competencies required for members who provide ethical support in clinical ethics consultations - Fukaya, Motohiro; Ayabe, Takanori; Miura, Yukari; Itai, Koichiro (Journal of Clinical Ethics, 2023)
In clinical ethics consultations in Japan, activities are carried out to provide appropriate advice in order to assist concerned parties in resolving anxieties and conflicts, such as withholding or discontinuing treatment, supporting patient decision-making, and so on. The purpose of this study is to conduct semi-structured interviews with senior clinical ethicists to clarify their competencies. The participants were 38 people from 20 medical institutions. Using theme analysis, 49 subcategories, 11 categories, and 4 themes were extracted from the verbatim transcripts. Clinical ethicists listens to the client’s anxieties regardless of their own perspective, sees through to the essence of the problem, and builds ethical reasoning. They support the discussion process itself in order to activate the exchange of opinions among participants through conferences and derive concrete measures for resolution. Above all, it is important to divide roles and promote cooperation within the ethics consulting team in order to demonstrate individual abilities. It was deduced from the narrative that they used a wide variety of competencies to support medical staff facing ethical issues.